2006
DOI: 10.1002/app.23422
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyalkylation of 6‐aminouracil

Abstract: Reactions of 6-aminouracil with formaldehyde, ethylene and propylene oxide, and ethylene carbonate were studied. Hydroxyalkyl derivatives of 6-aminouracil were prepared. The structure of the products were established by elemental analysis, 1 H-NMR, and IR techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 12 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…Those investigations also showed that 6-AU reacts with excess oxiranes [ethylene oxide (EO) and propylene oxide (PO)] in dimethylsulfoxide (DMSO) solution in the presence of triethylamine (TEA) as a catalyst, yielding the appropriate hydroxyalkyl derivatives. 1,2 Hydroxyethyl derivatives can be produced in reactions of 6-AU with ethylene carbonate as well. 6-AU in the presence of potassium carbonate or 1,4-diazabicyclo[2,2,2]octane dissolves in hot ethylene carbonate (1608C) and reacts with this reagent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those investigations also showed that 6-AU reacts with excess oxiranes [ethylene oxide (EO) and propylene oxide (PO)] in dimethylsulfoxide (DMSO) solution in the presence of triethylamine (TEA) as a catalyst, yielding the appropriate hydroxyalkyl derivatives. 1,2 Hydroxyethyl derivatives can be produced in reactions of 6-AU with ethylene carbonate as well. 6-AU in the presence of potassium carbonate or 1,4-diazabicyclo[2,2,2]octane dissolves in hot ethylene carbonate (1608C) and reacts with this reagent.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 We identified the products of the reaction between 6-AU and formaldehyde as hydroxymethyl derivatives of structure: where x ¼ 1, y ¼ 0, or x þ y ¼ 3. Those investigations also showed that 6-AU reacts with excess oxiranes [ethylene oxide (EO) and propylene oxide (PO)] in dimethylsulfoxide (DMSO) solution in the presence of triethylamine (TEA) as a catalyst, yielding the appropriate hydroxyalkyl derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary tests have shown that EC reacts with 6aminouracil (6-AU), giving hydroxyalkyl deriva-tives. 12,13 Here the results of investigations of the reactions of 6-AU with EC to obtain polyetherols with 1,3-pyrimidine rings are described.…”
Section: Introductionmentioning
confidence: 99%
“…Polyetherols with 1,3-pyrimidine rings [Formula (I)] can be used to produce polyurethane foams of improved thermal stability [1]. So far these polyetherols were obtained in the reactions of 6-aminouracil (6-AU) with excess of oxiranes such as ethylene oxide (EO) or propylene oxide (PO) [2][3][4].…”
mentioning
confidence: 99%
“…Instead of oxiranes, non-flammable and non-toxic ethylene carbonate (EC) was used, which was both the solvent and reagent. It has been found recently, that EC reacts similarly to EO with formation of polyetherols, as in case of the reaction of 6-AU with EO [2][3][4][5]. It has also been demonstrated that PO in reactions with melamine [6], isocyanuric acid [7] or uric acid [8] can be replaced with propylene carbonate (PC) to obtain polyetherols, in which heterocyclic rings are connected with oxypropylene groups.…”
mentioning
confidence: 99%